2005
DOI: 10.1021/ja055883e
|View full text |Cite
|
Sign up to set email alerts
|

An Annulation toward Fused Bicyclolactones

Abstract: We have now determined that the mutant designated P86A in this paper is, in actuality, P56A. We attribute this error to a visual mistracking along the DNA sequence, such that primers were constructed to alter the proline at position 56. P56 lies on a surface-exposed loop in the substrate-binding domain, ca. 18 Å away from the bound trifluoroethanol; the corresponding position is either deleted or a proline in the mesophilic and psychrophilic alcohol dehydrogenases, respectively. A comparison of the properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…More recently, the same group has developed a new route to fused lactones, the synthesis of which are based on a cascade addition of b-ketoesters to a cyclic diene followed by an in situ lactonization; the reactions are catalyzed by a combination of Lewis acid and Brønsted acid, GaA C H T U N G T R E N N U N G (OTf) 3 /HOTf. [7] Most of the recent studies of the catalytic addition of b-dicarbonyl compounds to olefins or polyenes are based on palladium, coinage metals, such as silver and gold, and gallium; however, the catalytic activities of other transition metals for this reaction have scarcely been investigated. Reported here is our work on the ruthenium-catalyzed addition of bdiketones to alcohols and styrenes.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the same group has developed a new route to fused lactones, the synthesis of which are based on a cascade addition of b-ketoesters to a cyclic diene followed by an in situ lactonization; the reactions are catalyzed by a combination of Lewis acid and Brønsted acid, GaA C H T U N G T R E N N U N G (OTf) 3 /HOTf. [7] Most of the recent studies of the catalytic addition of b-dicarbonyl compounds to olefins or polyenes are based on palladium, coinage metals, such as silver and gold, and gallium; however, the catalytic activities of other transition metals for this reaction have scarcely been investigated. Reported here is our work on the ruthenium-catalyzed addition of bdiketones to alcohols and styrenes.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, we have shown that gallium (III) trifluoromethanesulfonate [Ga(OTf) 3 , gallium triflate], acts as an effective but mild and water tolerant Lewis acid catalyst for many organic synthetic transformations such as Friedel-Crafts alkylations, dehydration of oximes to the corresponding nitriles, Beckman rearrangement, etc. [44][45][46][47][48][49][50][51][52]. We also found that gallium triflate offers the optimum acidity required for ketonic Strecker reaction [53] and the synthesis of various heterocycles such as dihydrobenzimidazolines, benzothiazolines, benzoxazinones etc.…”
Section: Introductionmentioning
confidence: 69%
“…However, optimized reaction conditions were accomplished using Bi(OTf) 3 /TfOH as an alternative catalytic system due to the fact that extensive decomposition of starting material was observed using gold catalysts. Some other studies were carried out trying to expand the hydroalkylation of olefins with β-ketoesters mediated by auric cations; however, they were clearly unsuccessful [ 50 ]; furthermore, in some conditions, the gold catalysts exhibited an unusual oxophilic behavior [ 51 ].…”
Section: Resultsmentioning
confidence: 99%